DRP (DRUG RELATED PROBLEM) MENURUT KLASIFIKASI CIPOLLEPADA PENYAKIT DIABETES TIPE 2 + HIPERTENSI - Hazizah Octarisa; Minanda Nashwa Junelfa; Nova Adelia Ber Tamba; Yenni Diila Anggraeni4; Shafira Zifa (SUAN PUBLISHER, 2025)
Drug Related Problems (DRP) are a significant challenge in the management of patients with comorbidities, potentially affecting therapeutic efficacy and clinical outcomes. This study aims to identify and classify DRP based on the Cipolle Classification in patients with Type 2 Diabetes Mellitus (T2DM) and Hypertension in health facilities (mention the type or name of the facility, e.g.: Hospital X or Health Center Y) in [mention the location, e.g.: City/Regency Z]. The study design is descriptive observational with a retrospective approach using medical record data from patients who meet the inclusion criteria (patients with T2DM and hypertension) during the period [mention the time range, e.g.: January 2024–June 2025]. The study sample will involve [number of samples, e.g.: 150] relevant patient medical records. DRPs will be identified from demographic data, medication history, physical examination results, and laboratory data, then categorized based on the Cipolle Classification, covering issues such as the need for additional therapy, ineffective drugs, too low or high doses, drug side effects, drug interactions, and patient non-compliance. The expected results will show the prevalence and types of DRPs most frequently found in this patient population, especially related to the complexity of the drug regimen, interactions of antihypertensive and antidiabetic drugs, and dose adjustments. This study is expected to provide crucial information for health workers, especially pharmacists, in optimizing pharmacotherapy management, improving patient safety, and ultimately improving the quality of life of T2DM patients with hypertension complications.